Keterkaitan Teknologi Informasi, Pembelajaran Organisasi, Kemampuan Manajemen Pengetahuan, Dan Kinerja Perusahaan - Sunardi Sunardi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The purpose of the study was to test empirically the influence of information technology relatedness and organizational learning on knowledge management ability and company performance either directly or indirectly. Research was expected to provide theoretical and practice contributions in banking management. The research instrument used a questionnaire that given to the head of bank branches in Palembang. Sampling technique used purposive sampling with the number of respondents 199 respondents. The result of the study showed that: the influence of information technology relatedness on organizational learning, the influence of organizational learning on knowledge management ability, the influence of knowledge management ability on company performance, to produce positive and significant influence, while the influence of information technology relatedness to knowledge management ability, the influence of information technology relatedness on corporate performance, the influence of organizational learning on company performance produced negative influence. The limitations of the study did not distinguish the market share and the level of banking competition.